Bioproduction of Alcohol by Ascomycetous Yeast Exposed to Some Chemical Mutagens - Singh, S.P.; Ambasta, B.K.; Rathor, Nalini (Asian Journal of Chemistry, 2010)
Mutagenic actions of o-, m-, p-tolyl hydrazine hydrochloride and 2,3,5,6-tetrafluorophenyl hydrazine were studied on fermentative production of alcohol by S. cerevisiae Am-38. It was found that ortho and meta-tolyl hydrazine hydrochloride greatly influences the production of alcohol while para-tolyl hydrazine hydrochloride and 2,3,5,6-tetrafluorophenyl hydrazine was not encouraging and could increase a slight alcohol in comparison to control.